A degradable lignin fiber material and preparation method thereof

By adding modified polyester to the degradable lignin fiber material and modifying lignin, the problems of poor heat aging resistance and low strength are solved, and the anti-photoaging performance is improved and the service life is extended.

CN118374907BActive Publication Date: 2025-02-07JIANGSU SHUONANG NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410664032.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-02-07
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

The existing degradable lignin fiber materials have poor thermal aging resistance and low strength, and insufficient photoaging resistance, which limits their service life.

Method used

By adding modified polyester to the lignin fiber material and modifying the lignin, it can undergo click reaction and self-crosslinking during the melt preparation process, improving mechanical properties and heat-resistant aging properties, while activating lignin Increases anti-UV and anti-oxidation properties.

Benefits of technology

The good heat-resistant aging performance, mechanical properties and photo-aging resistance of the degradable lignin fiber material are achieved, which extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004860565730000111
    Figure BDA0004860565730000111
Patent Text Reader

Abstract

The present invention relates to the technical field of degradable materials, and in particular to a degradable lignin fiber material and a preparation method thereof. The degradable lignin fiber material comprises the following raw materials in parts by weight: 80-100 parts of polylactic acid, 10-15 parts of modified polyester and 30-40 parts of modified lignin. The modified polyester is added into the lignin fiber material, and the lignin fiber is modified. The modified polyester and the modified lignin are cross-linked to each other, so that the base materials have good compatibility, and the degradable lignin fiber material has good heat aging resistance and mechanical properties. Since anti-aging groups are introduced into the modified lignin, the modified lignin also has good light aging resistance, so that the modified lignin has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of degradable materials, and in particular to a degradable lignin fiber material and a preparation method thereof. Background Art

[0002] Polylactic acid is a bio-based degradable polymer material obtained by polymerization of lactic acid prepared by fermentation of biomass raw materials. It has the characteristics of easy processing and high strength. It has been widely used in biomedicine, fiber spinning, food packaging and other fields. However, polylactic acid has defects such as high brittleness and poor heat aging resistance, which limits its application range. Lignin is the second largest renewable biomass in nature after cellulose. It has a phenylpropane unit as a skeleton and contains multiple functional groups such as hydroxyl and methoxy. It is widely present in plants. At the same time, lignin is a natural anti-ultraviolet protective agent with great application potential. The conjugated structures such as benzene rings, carbonyl groups, and double bonds in lignin molecules can absorb ultraviolet rays, and phenolic hydroxyl groups can effectively scavenge free radicals. However, the degree of conjugation in lignin molecules is low and the absorption of long-wave ultraviolet rays with cumulative damage is insufficient, resulting in its long-term insufficient anti-ultraviolet absorption ability, which limits its further development and application as an anti-ultraviolet protective agent.

[0003] Polylactic acid and lignin are both degradable materials. It is a common modification method to blend lignin and polylactic acid to prepare composite materials. However, due to the properties of lignin itself, it is easy to agglomerate and has poor compatibility with the matrix, and its efficient utilization cannot be achieved. Although lignin has certain anti-ultraviolet protection properties, polylactic acid lignin composite materials, like other wood-plastic composite materials, will undergo light aging under certain environmental conditions, causing the composite material or the fiber / matrix interface to be damaged, the mechanical properties of the composite material to be reduced, and the service life to be affected. Summary of the invention

[0004] The purpose of the present invention is to provide a degradable lignin fiber material and a preparation method thereof, which solves the problems of poor heat aging resistance and low strength of existing degradable lignin fiber materials, and at the same time, it also has good light aging resistance, so that it has a longer service life.

[0005] The purpose of the present invention can be achieved by the following technical scheme: a degradable lignin fiber material is prepared by the following steps: weighing the following raw materials by weight: 80-100 parts of polylactic acid, 10-15 parts of modified polyester and 30-40 parts of modified lignin, mixing the polylactic acid, modified polyester and modified lignin, adding them to a twin-screw extruder, melt spinning, stretching, deforming, and rotating to obtain a degradable lignin fiber material;

[0006] The modified polyester is prepared by the following steps:

[0007] Step A1: 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and tetrahydrofuran were mixed, and 3-bromo-1-propylene was added under stirring at a rate of 240-300 rpm and room temperature, and the mixture was reacted for 24 hours to obtain intermediate 1; intermediate 1, methanol and hydrochloric acid solution were mixed, and the mixture was reacted for 2-4 hours under stirring at a rate of 240-300 rpm and room temperature to obtain intermediate 2;

[0008] The amount ratio of 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and 3-bromo-1-propylene is 0.1-0.12 mol: 5.5-6 g: 0.12-0.14 mol, the molar concentration of the hydrochloric acid solution is 1 mol / L, and the amount ratio of the intermediate 1 and the hydrochloric acid solution is 0.1-0.12 mol: 150-200 mL;

[0009] During the reaction, the alcoholic hydroxyl group in 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane undergoes etherification reaction with the bromine in 3-bromo-1-propylene to obtain intermediate 1. The diacetal structure in intermediate 1 is hydrolyzed under acidic conditions to form a hydroxyl group to obtain intermediate 2.

[0010] Step A2: Intermediate 2, caprolactone, stannous octoate and toluene are mixed, and the mixture is reacted for 24 hours at a stirring rate of 500-600 rpm and a temperature of 120° C. to obtain polyester;

[0011] The ratio of intermediate 2, caprolactone and stannous octoate is 0.04-0.05 mol: 0.08-0.1 mol: 1-1.2 g;

[0012] During the reaction, under the action of stannous octoate, the caprolactone ring is opened and polymerized starting from the hydroxyl group in the intermediate 2 to obtain a polyester with hydroxyl groups at both ends;

[0013] Step A3: 1,3-acetone dimethyl dicarboxylate, chloroacetaldehyde, pyridine and deionized water were mixed, and the mixture was reacted for 48 hours at a stirring rate of 240-300 rpm and a temperature of 50° C. to obtain intermediate 3; intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate were mixed, and the mixture was reacted for 3-4 hours at a stirring rate of 500-600 rpm and a temperature of 170° C. under nitrogen protection; the nitrogen protection was removed, the mixture was heated to 240° C. and vacuumed to 0.04 mbar; the reaction was continued for 4-6 hours to obtain modified polyester;

[0014] The amount ratio of dimethyl 1,3-acetone dicarboxylate, chloroacetaldehyde and pyridine is 0.14-0.16 mol: 0.14 mol: 40-50 mL, and the amount ratio of intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate is 0.14-0.16 mol: 0.3-0.4 mol: 20-24 g: 0.2 g;

[0015] During the reaction, the ketone group in 1,3-acetone dicarboxylic acid dimethyl ester reacts with chloroacetaldehyde to form an intermediate 3 containing a furan group and an ester group. Under the action of tetrabutyl titanate, an ester exchange reaction occurs between the intermediate 3, 1,4-butanediol and polyester to obtain a modified polyester.

[0016] The modified lignin is prepared by the following steps:

[0017] Step B1: diethanolamine and paraformaldehyde are mixed, and 2,4-dihydroxybenzophenone and methanol are added under stirring at a rate of 300-400 rpm and a temperature of 85°C, and the mixture is reacted for 3-4 hours to obtain intermediate a; intermediate a, 3-(triphenylmethylthio)propionic acid and acetone are mixed, and dicyclohexylcarbodiimide is added under stirring at a rate of 300-400 rpm and a temperature of 85°C, and the mixture is reacted for 24 hours to obtain intermediate b;

[0018] The ratio of diethanolamine, paraformaldehyde and 2,4-dihydroxybenzophenone is 0.02-0.03 mol: 0.02-0.03 mol: 0.01-0.012 mol, and the ratio of intermediate a, 3-(tritylthio)propionic acid and dicyclohexylcarbodiimide is 0.01-0.012 mol: 0.024-0.028 mol: 9-10 g;

[0019] During the reaction, 2,4-dihydroxybenzophenone is formylated under the action of polyformaldehyde to form a formyl group between its ortho-phenolic hydroxyl groups, and the formyl group reacts with the secondary amine in diethanolamine to obtain intermediate a, and then the hydroxyl group in intermediate a reacts with 3-(triphenylmethylthio)propionic acid under the action of dicyclohexylcarbodiimide to obtain intermediate b.

[0020] Step B2: Mix intermediate b, triethylamine and tetrahydrofuran, stir under nitrogen protection, at a stirring rate of 120-180 rpm and a temperature of 5°C, add bromoacetyl bromide, and react for 6-8 hours to obtain intermediate c;

[0021] The ratio of intermediate b, triethylamine and bromoacetyl bromide is 0.01-0.012 mol: 3-3.2 g: 0.01 mol;

[0022] During the reaction, the phenolic hydroxyl group in the intermediate b reacts with the acyl bromide group in bromoacetyl bromide to form an ester group, and at the same time, the trityl group in the tritylthio group is deprotected to form a thiol group, thereby obtaining the intermediate c;

[0023] Step B3: Mix lignin and N,N-dimethylformamide, stir at a rate of 300-400 rpm, and add iodocyclohexane at a temperature of 130°C, and react for 3-4 hours to obtain activated lignin; mix intermediate c and tetrahydrofuran and adjust the pH value to 11, stir at a rate of 300-400 rpm, and add activated lignin at a temperature of 80°C, and react for 8-10 hours to obtain modified lignin;

[0024] The ratio of lignin to iodocyclohexane is 0.5-0.6 g: 3.5-4 mL, and the ratio of intermediate c to activated lignin is 0.001-0.0012 mol: 4-6 g;

[0025] During the reaction, lignin undergoes a demethylation reaction under the action of iodocyclohexane to form phenolic hydroxyl groups, and the bromine in the intermediate c then undergoes an etherification reaction with the phenolic hydroxyl groups in the activated lignin to obtain modified lignin.

[0026] Beneficial effects of the invention: The invention relates to a degradable lignin fiber material and a preparation method thereof. By adding modified polyester into the lignin fiber material and modifying the lignin fiber, the degradable lignin fiber material has good heat aging resistance and mechanical properties, and also has good light aging resistance, so that it has a long service life; in the melt preparation process of the degradable lignin fiber material, since the modified polyester contains side chain double bonds, and the lignin is modified so that the modified lignin contains thiol groups, during the melt extrusion process, the thiol groups react with the double bonds to form cross-linked connections between the modified polyester and the modified lignin, and since the modified polyester contains polyester segments, it has good compatibility with the polylactic acid matrix, so that the degradable lignin fiber material has good mechanical properties, and since the modified polyester contains an intermediate 3 containing a furan group, during the melt preparation process of the degradable lignin fiber material, a small part of the furan groups undergo ring opening to form aldehyde groups containing ketoglutaric acid structures, so that self-crosslinking behavior occurs in the matrix, thereby improving the degradable lignin The mechanical properties of the fiber material, and because the modified polyester contains rigid furan groups, it also improves the heat aging resistance of the degradable lignin fiber material to a certain extent. By demethylating the lignin, the lignin has more phenolic hydroxyl structures, which have good reaction activity and are also important anti-ultraviolet and anti-oxidation functional group structures of lignin. The anti-ultraviolet and anti-oxidation properties of the modified lignin are further improved by activation, and more reaction nodes are provided to participate in the next reaction. At the same time, because the intermediate c contains a benzophenone structure, the intermediate c is grafted onto the activated lignin, and the benzophenone structure forms a chelate ring structure through intramolecular hydrogen bonds. When the molecule absorbs the energy of ultraviolet radiation, the molecule undergoes proton transfer, the hydrogen bond breaks, and an enol structure is formed. The absorbed light energy can be released in the form of heat energy, and the molecule will also recover from the excited state to the ground state again. This recoverable conjugated structure gives the modified cellulose continuous anti-ultraviolet ability, so that the degradable lignin fiber material has long-term good antioxidant and anti-ultraviolet properties, thereby ensuring that the degradable lignin fiber material has a long service life. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1 A degradable lignin fiber material is prepared by the following steps: weigh the following raw materials in parts by weight: 80 parts of UPM 11000 polylactic acid, 10 parts of modified polyester and 30 parts of modified lignin, mix the polylactic acid, modified polyester and modified lignin, add them to a twin-screw extruder, melt-spin, stretch, deform and rotate to obtain a degradable lignin fiber material;

[0029] The modified polyester is prepared by the following steps:

[0030] Step A1: 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and tetrahydrofuran were mixed, and 3-bromo-1-propylene was added under stirring at a rate of 240 rpm and room temperature, and the mixture was reacted for 24 hours to obtain intermediate 1; intermediate 1, methanol and hydrochloric acid solution were mixed, and the mixture was reacted for 4 hours under stirring at a rate of 240 rpm and room temperature to obtain intermediate 2;

[0031] The ratio of 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and 3-bromo-1-propylene is 0.1 mol:5.5 g:0.12 mol, the molar concentration of the hydrochloric acid solution is 1 mol / L, and the ratio of the intermediate 1 to the hydrochloric acid solution is 0.1 mol:150 mL;

[0032] Step A2: Intermediate 2, caprolactone, stannous octoate and toluene are mixed, and the mixture is reacted for 24 hours at a stirring rate of 500 rpm and a temperature of 120° C. to obtain polyester;

[0033] The ratio of intermediate 2, caprolactone and stannous octoate is 0.04 mol: 0.08 mol: 1 g;

[0034] Step A3: 1,3-acetone dicarboxylic acid dimethyl ester, chloroacetaldehyde, pyridine and deionized water were mixed, and the mixture was reacted for 48 hours at a stirring rate of 240 rpm and a temperature of 50° C. to obtain intermediate 3; intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate were mixed, and the mixture was reacted for 4 hours at a stirring rate of 500 rpm and a temperature of 170° C. under nitrogen protection; the nitrogen protection was removed, the mixture was heated to 240° C. and vacuumized to 0.04 mbar; the reaction was continued for 6 hours to obtain modified polyester;

[0035] The amount ratio of dimethyl 1,3-acetone dicarboxylate, chloroacetaldehyde and pyridine is 0.14 mol: 0.14 mol: 40 mL, and the amount ratio of intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate is 0.14 mol: 0.3 mol: 20 g: 0.2 g;

[0036] The modified lignin is prepared by the following steps:

[0037] Step B1: diethanolamine and paraformaldehyde are mixed, and 2,4-dihydroxybenzophenone and methanol are added under stirring at a rate of 300 rpm and a temperature of 85°C, and the mixture is reacted for 4 hours to obtain intermediate a; intermediate a, 3-(triphenylmethylthio)propionic acid and acetone are mixed, and dicyclohexylcarbodiimide is added under stirring at a rate of 300 rpm and a temperature of 85°C, and the mixture is reacted for 24 hours to obtain intermediate b;

[0038] The ratio of diethanolamine, paraformaldehyde and 2,4-dihydroxybenzophenone was 0.02 mol: 0.02 mol: 0.01 mol, and the ratio of intermediate a, 3-(tritylthio)propionic acid and dicyclohexylcarbodiimide was 0.01 mol: 0.024 mol: 9 g;

[0039] Step B2: Mix the intermediate b, triethylamine and tetrahydrofuran, stir at a rate of 120 rpm and a temperature of 5°C under nitrogen protection, add bromoacetyl bromide, and react for 8 hours to obtain the intermediate c;

[0040] The ratio of intermediate b, triethylamine and bromoacetyl bromide is 0.01 mol: 3 g: 0.01 mol;

[0041] Step B3: UPM 190 lignin and N,N-dimethylformamide were mixed, stirred at a stirring rate of 300 rpm and a temperature of 130°C, iodocyclohexane was added, and the mixture was reacted for 4 hours to obtain activated lignin; intermediate c and tetrahydrofuran were mixed and the pH value was adjusted to 11, stirred at a stirring rate of 300 rpm and a temperature of 80°C, activated lignin was added, and the mixture was reacted for 10 hours to obtain modified lignin;

[0042] The ratio of lignin to iodocyclohexane was 0.5 g:3.5 mL, and the ratio of intermediate c to activated lignin was 0.001 mol:4 g.

[0043] Example 2 A degradable lignin fiber material is prepared by the following steps: weigh the following raw materials in parts by weight: 100 parts of UPM 11000 polylactic acid, 15 parts of modified polyester and 30 parts of modified lignin, mix the polylactic acid, modified polyester and modified lignin, add them to a twin-screw extruder, melt-spin, stretch, deform and rotate to obtain a degradable lignin fiber material;

[0044] The modified polyester is prepared by the following steps:

[0045] Step A1: 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and tetrahydrofuran were mixed, and 3-bromo-1-propylene was added under stirring at a rate of 300 rpm and room temperature, and the mixture was reacted for 24 hours to obtain intermediate 1. Intermediate 1, methanol and hydrochloric acid solution were mixed, and the mixture was reacted for 2 hours under stirring at a rate of 300 rpm and room temperature to obtain intermediate 2;

[0046] The amount ratio of 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and 3-bromo-1-propylene is 0.12 mol:5.5 g:0.14 mol, the molar concentration of the hydrochloric acid solution is 1 mol / L, and the amount ratio of the intermediate 1 and the hydrochloric acid solution is 0.12 mol:150 mL;

[0047] Step A2: Intermediate 2, caprolactone, stannous octoate and toluene are mixed, and the mixture is reacted for 24 hours at a stirring rate of 600 rpm and a temperature of 120° C. to obtain polyester;

[0048] The ratio of intermediate 2, caprolactone and stannous octoate is 0.04 mol: 0.08 mol: 1.2 g;

[0049] Step A3: 1,3-acetone dimethyl dicarboxylate, chloroacetaldehyde, pyridine and deionized water were mixed, and the mixture was reacted for 48 hours at a stirring rate of 300 rpm and a temperature of 50° C. to obtain intermediate 3. Intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate were mixed, and the mixture was reacted for 3 hours at a stirring rate of 600 rpm and a temperature of 170° C. under nitrogen protection. The nitrogen protection was removed, the mixture was heated to 240° C. and vacuumed to 0.04 mbar. The reaction was continued for 4 hours to obtain modified polyester.

[0050] The amount ratio of dimethyl 1,3-acetone dicarboxylate, chloroacetaldehyde and pyridine is 0.14 mol: 0.14 mol: 50 mL, and the amount ratio of intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate is 0.14 mol: 0.4 mol: 20 g: 0.2 g;

[0051] The modified lignin is prepared by the following steps:

[0052] Step B1: diethanolamine and paraformaldehyde are mixed, and 2,4-dihydroxybenzophenone and methanol are added under stirring at a rate of 400 rpm and a temperature of 85°C, and the mixture is reacted for 3 hours to obtain intermediate a; intermediate a, 3-(triphenylmethylthio)propionic acid and acetone are mixed, and dicyclohexylcarbodiimide is added under stirring at a rate of 400 rpm and a temperature of 85°C, and the mixture is reacted for 24 hours to obtain intermediate b;

[0053] The ratio of diethanolamine, paraformaldehyde and 2,4-dihydroxybenzophenone was 0.03 mol: 0.02 mol: 0.01 mol, and the ratio of intermediate a, 3-(tritylthio)propionic acid and dicyclohexylcarbodiimide was 0.012 mol: 0.024 mol: 9 g;

[0054] Step B2: Mix intermediate b, triethylamine and tetrahydrofuran, stir at a rate of 180 rpm and a temperature of 5°C under nitrogen protection, add bromoacetyl bromide, and react for 6 hours to obtain intermediate c;

[0055] The ratio of intermediate b, triethylamine and bromoacetyl bromide is 0.01 mol: 3.2 g: 0.01 mol;

[0056] Step B3: UPM 190 lignin and N,N-dimethylformamide were mixed, stirred at a stirring rate of 400 rpm and a temperature of 130°C, iodocyclohexane was added, and the mixture was reacted for 3 hours to obtain activated lignin; intermediate c and tetrahydrofuran were mixed and the pH value was adjusted to 11, stirred at a stirring rate of 400 rpm and a temperature of 80°C, activated lignin was added, and the mixture was reacted for 8 hours to obtain modified lignin;

[0057] The ratio of lignin to iodocyclohexane was 0.5 g:3.5 mL, and the ratio of intermediate c to activated lignin was 0.0012 mol:4 g.

[0058] Example 3 A degradable lignin fiber material is prepared by the following steps: weigh the following raw materials in parts by weight: 100 parts of UPM 11000 polylactic acid, 15 parts of modified polyester and 40 parts of modified lignin, mix the polylactic acid, modified polyester and modified lignin, add them to a twin-screw extruder, melt-spin, stretch, deform and rotate to obtain a degradable lignin fiber material;

[0059] The modified polyester is prepared by the following steps:

[0060] Step A1: 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and tetrahydrofuran were mixed, and 3-bromo-1-propylene was added under stirring at a rate of 300 rpm and room temperature, and the mixture was reacted for 24 hours to obtain intermediate 1. Intermediate 1, methanol and hydrochloric acid solution were mixed, and the mixture was reacted for 4 hours under stirring at a rate of 300 rpm and room temperature to obtain intermediate 2;

[0061] The amount ratio of 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and 3-bromo-1-propylene is 0.12 mol:6 g:0.14 mol, the molar concentration of the hydrochloric acid solution is 1 mol / L, and the amount ratio of the intermediate 1 and the hydrochloric acid solution is 0.12 mol:200 mL;

[0062] Step A2: Intermediate 2, caprolactone, stannous octoate and toluene are mixed, and the mixture is reacted for 24 hours at a stirring rate of 600 rpm and a temperature of 120° C. to obtain polyester;

[0063] The ratio of intermediate 2, caprolactone and stannous octoate is 0.05 mol: 0.1 mol: 1.2 g;

[0064] Step A3: 1,3-acetone dimethyl dicarboxylate, chloroacetaldehyde, pyridine and deionized water were mixed, and the mixture was reacted for 48 hours at a stirring rate of 300 rpm and a temperature of 50° C. to obtain intermediate 3; intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate were mixed, and the mixture was reacted for 4 hours at a stirring rate of 600 rpm and a temperature of 170° C. under nitrogen protection; the nitrogen protection was removed, the mixture was heated to 240° C. and vacuumed to 0.04 mbar; the reaction was continued for 6 hours to obtain modified polyester;

[0065] The amount ratio of dimethyl 1,3-acetone dicarboxylate, chloroacetaldehyde and pyridine is 0.16 mol: 0.14 mol: 50 mL, and the amount ratio of intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate is 0.16 mol: 0.4 mol: 24 g: 0.2 g;

[0066] The modified lignin is prepared by the following steps:

[0067] Step B1: diethanolamine and paraformaldehyde are mixed, and 2,4-dihydroxybenzophenone and methanol are added under stirring at a rate of 400 rpm and a temperature of 85°C, and the mixture is reacted for 4 hours to obtain intermediate a; intermediate a, 3-(triphenylmethylthio)propionic acid and acetone are mixed, and dicyclohexylcarbodiimide is added under stirring at a rate of 400 rpm and a temperature of 85°C, and the mixture is reacted for 24 hours to obtain intermediate b;

[0068] The ratio of diethanolamine, paraformaldehyde and 2,4-dihydroxybenzophenone is 0.03 mol: 0.03 mol: 0.012 mol, and the ratio of intermediate a, 3-(tritylthio)propionic acid and dicyclohexylcarbodiimide is 0.012 mol: 0.028 mol: 10 g;

[0069] Step B2: Mix intermediate b, triethylamine and tetrahydrofuran, stir under nitrogen protection at a stirring rate of 180 rpm and a temperature of 5°C, add bromoacetyl bromide, and react for 8 hours to obtain intermediate c;

[0070] The ratio of intermediate b, triethylamine and bromoacetyl bromide is 0.012 mol: 3.2 g: 0.01 mol;

[0071] Step B3: UPM 190 lignin and N,N-dimethylformamide were mixed, stirred at a stirring rate of 400 rpm and a temperature of 130°C, iodocyclohexane was added, and the mixture was reacted for 4 hours to obtain activated lignin; intermediate c and tetrahydrofuran were mixed and the pH value was adjusted to 11, stirred at a stirring rate of 400 rpm and a temperature of 80°C, activated lignin was added, and the mixture was reacted for 10 hours to obtain modified lignin;

[0072] The ratio of lignin to iodocyclohexane was 0.6 g:4 mL, and the ratio of intermediate c to activated lignin was 0.0012 mol:6 g.

[0073] Comparative Example 1 Compared with Example 3, this comparative example replaces 3-bromo-1-propylene with n-propyl bromide in the preparation process of the modified polyester in Example 3, and the other steps are the same.

[0074] Comparative Example 2 Compared with Example 3, this comparative example is characterized in that the intermediate 3 in the preparation process of the modified polyester in Example 3 is replaced by diethyl adipate, and the other steps are the same.

[0075] Comparative Example 3 Compared with Example 3, this comparative example is characterized in that the activated lignin in the modified cellulose preparation process of Example 3 is replaced by UPM 190 lignin, and the other steps are the same.

[0076] Comparative Example 4 Compared with Example 3, this comparative example is to remove the intermediate c in the preparation process of modified cellulose in Example 3, and the other steps are the same.

[0077] The degradable lignin fiber materials prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested for tensile properties according to the standard GB / T 14344-2022. The pre-tension was 0.05 cN / dtex, the clamping distance was 250 mm, the tensile rate was 1000 mm / min, and the sample was placed at a temperature of 80°C and a humidity of 95% for a heat aging time of 720 h, and then its tensile strength was measured. The sample was placed in a dry sealed bag and placed in an outdoor environment with direct sunlight for 168 h / 720 h, and then its tensile strength was measured. The test results are shown in Table 1 below:

[0078] Table 1

[0079]

[0080] It can be seen from the test results in the table shown that when Example 7, Example 8 and Example 9 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces 3-bromo-1-propylene with n-propyl bromide in the preparation process of the modified polyester in Example 3. Due to the lack of covalent bond connection between the modified polyester and the modified lignin, the mechanical properties and heat aging resistance of the degradable lignin fiber material are significantly reduced. Comparative Example 2 replaces intermediate 3 in the preparation process of the modified polyester in Example 3 with diethyl adipate. Due to the lack of furan groups in the modified polyester, its mechanical properties are reduced to a certain extent. Comparative Example 3 replaces the modified polyester in Example 3 with diethyl adipate. During the preparation of cellulose, activated lignin is replaced by lignin. Due to the lack of active group reaction nodes and antioxidant and anti-ultraviolet functional groups, namely phenolic hydroxyl groups, in the modified lignin, its anti-light aging performance decreases to a certain extent. In Comparative Example 4, intermediate c in the preparation process of modified cellulose in Example 3 is removed. Due to the lack of benzophenone structure, although the anti-light aging performance does not show a significant decrease at 168h, its anti-light aging performance shows a significant decrease at 720h, indicating that the introduction of intermediate c enables the modified cellulose to continue to resist ultraviolet rays, thereby making the degradable lignin fiber material have long-term good antioxidant and anti-ultraviolet properties.

[0081] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a degradable lignin fiber material, characterized in that: The method is prepared by the following steps: weighing the following raw materials by weight: 80-100 parts of polylactic acid, 10-15 parts of modified polyester and 30-40 parts of modified lignin, mixing the polylactic acid, modified polyester and modified lignin, adding the mixture to a twin-screw extruder at an extrusion temperature of 180° C., and then performing injection molding by an injection molding machine at an injection molding temperature of 185° C. and an injection molding pressure of 0.6 MPa, to obtain a degradable lignin fiber material; The modified polyester is prepared by the following steps: Step A1: 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and tetrahydrofuran are mixed, stirred at a stirring rate of 240-300 rpm and room temperature, and 3-bromo-1-propylene is added, and the mixture is reacted for 24 hours to obtain intermediate 1; intermediate 1, methanol and hydrochloric acid solution are mixed, stirred at a stirring rate of 240-300 rpm and room temperature, and the mixture is reacted for 2-4 hours to obtain intermediate 2; Step A2: Intermediate 2, caprolactone, stannous octoate and toluene are mixed, and the mixture is reacted for 24 hours at a stirring rate of 500-600 rpm and a temperature of 120° C. to obtain polyester; Step A3: 1,3-acetone dimethyl dicarboxylate, chloroacetaldehyde, pyridine and deionized water were mixed, and the mixture was reacted for 48 hours at a stirring rate of 240-300 rpm and a temperature of 50° C. to obtain intermediate 3; intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate were mixed, and the mixture was reacted for 3-4 hours at a stirring rate of 500-600 rpm and a temperature of 170° C. under nitrogen protection; the nitrogen protection was removed, the mixture was heated to 240° C. and vacuumed to 0.04 mbar; the reaction was continued for 4-6 hours to obtain modified polyester; The modified lignin is prepared by the following steps: Step B1: diethanolamine and paraformaldehyde are mixed, and 2,4-dihydroxybenzophenone and methanol are added under stirring at a rate of 300-400 rpm and a temperature of 85°C, and the mixture is reacted for 3-4 hours to obtain an intermediate a; intermediate a, 3-(triphenylmethylthio)propionic acid and acetone are mixed, and dicyclohexylcarbodiimide is added under stirring at a rate of 300-400 rpm and a temperature of 85°C, and the mixture is reacted for 24 hours to obtain an intermediate b; Step B2: Mix intermediate b, triethylamine and tetrahydrofuran, stir under nitrogen protection, at a stirring rate of 120-180 rpm and a temperature of 5°C, add bromoacetyl bromide, and react for 6-8 hours to obtain intermediate c; Step B3: Mix lignin and N,N-dimethylformamide, stir and add iodocyclohexane at a stirring rate of 300-400 rpm and a temperature of 130°C, and react for 3-4 hours to obtain activated lignin. Mix intermediate c and tetrahydrofuran and adjust the pH value to 11. Stir and add activated lignin at a stirring rate of 300-400 rpm and a temperature of 80°C, and react for 8-10 hours to obtain modified lignin.

2. The method for preparing a degradable lignin fiber material according to claim 1, characterized in that: In step A1: the ratio of 5,5-bis(hydroxymethyl)-2-phenyl-1,3-dioxane, sodium hydroxide and 3-bromo-1-propylene is 0.1-0.12 mol: 5.5-6 g: 0.12-0.14 mol, the molar concentration of the hydrochloric acid solution is 1 mol / L, and the ratio of the intermediate 1 to the hydrochloric acid solution is 0.1-0.12 mol: 150-200 mL.

3. The method for preparing a degradable lignin fiber material according to claim 2, characterized in that: In step A2: the usage ratio of intermediate 2, caprolactone and stannous octoate is 0.04-0.05 mol: 0.08-0.1 mol: 1-1.2 g.

4. The method for preparing a degradable lignin fiber material according to claim 2, characterized in that: In step A3: the usage ratio of dimethyl 1,3-acetonedicarboxylate, chloroacetaldehyde and pyridine is 0.14-0.16 mol: 0.14 mol: 40-50 mL, and the usage ratio of intermediate 3, 1,4-butanediol, polyester and tetrabutyl titanate is 0.14-0.16 mol: 0.3-0.4 mol: 20-24 g: 0.2 g.

5. The method for preparing a degradable lignin fiber material according to claim 2, characterized in that: In step B1, the ratio of diethanolamine, paraformaldehyde and 2,4-dihydroxybenzophenone is 0.02-0.03 mol: 0.02-0.03 mol: 0.01-0.012 mol, and the ratio of intermediate a, 3-(tritylthio)propionic acid and dicyclohexylcarbodiimide is 0.01-0.012 mol: 0.024-0.028 mol: 9-10 g.

6. The method for preparing a degradable lignin fiber material according to claim 1, characterized in that: In step B2: the ratio of the intermediate b, triethylamine and bromoacetyl bromide is 0.01-0.012 mol: 3-3.2 g: 0.01 mol.

7. The method for preparing a degradable lignin fiber material according to claim 6, characterized in that: In step B3: the ratio of lignin to iodocyclohexane is 0.5-0.6 g: 3.5-4 mL, and the ratio of intermediate c to activated lignin is 0.001-0.0012 mol: 4-6 g.

8. A degradable lignin fiber material, characterized in that: Prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Fiber-based degradable film and preparation method thereof

    CN114479139A

  • High-moisture-absorption ITY composite fiber and preparation method thereof

    CN116926730A